(untitled) (Eurasian Research Bulletin, 2022)
In this article, the author aims to identify the pedagogical skills of the most effective use of innovative technologies in the process of teaching the methodology of teaching the long jump technique for students of universities of all directions. The analysis of bibliographic data of researchers is given. The article proposes a system of exercises and tasks related to the use of graphic organizers, Venn Diagrams, the conceptual table "ZHU" and the case method in the classroom for the course "Physical Education".